HOW CLOSELY IS PROTEIN CARBONYL (PCO) LEVEL CORRELATED WITH SEPSIS-RELATED ORGAN FUNCTION ASSESSMENT (SOFA) SCORE? - LESTARI, MAYANG INDAH; SEDONO, RUDYANTO; ZULKIFLI; MARITSKA, ZISKE (International Journal of Applied Pharmaceutics, 2020)
Objective: Sepsis remains an unsolved problem in hospitals since its mortality rate is not significantly reduced despite considerable therapy efforts. The most used prognostic tool is the Sepsis-related Organ Function (SOFA) score, which requires several clinical and laboratory examinations; our recent studies also showed that the protein carbonyl level (PCO) has prognostic value in predicting sepsis mortality. Methods: This prospective study was designed to assess the correlation between PCO values and the SOFA score following ethical approval. Adult patients aged>18 y who met the Sepsis-3 definition were included. Exclusion criteria were patients not admitted to the intensive care unit. Dropout criteria included mortality within the 1h bundle protocol. Baseline demographic data and blood collection were measured for all subjects. Subjects were treated with the 1h bundle protocol and observed for 28 d. Results: Fifty-nine subjects were included, with no significant differences in age, sex, diagnosis, microbiology or Charlson’s Comorbidity score between survivors and non-survivors. The SOFA score was higher in non-survivors (10.90±3.38 vs 8.11±3.07; p=0.003), as was the PCO value (24.5 [14.67-81] vs 18 [15-21.33]; p<0.001). However, the correlation between PCO and SOFA score is very weak (r=0.101; p=0.45). Conclusion: Both the PCO level and SOFA scores were higher in non-survivor septic patients. However, they have a very weak correlation and cannot be used interchangeably.